PERANCANGAN TAMAN REKREASI KELUARGA DIKAWASAN TEPIAN SUNGAI MAHAKAM KOTA SAMARINDA - YONO, PAR (KURVA S JURNAL MAHASISWA, 2013)
Tourism busniness is one of potential sector that give contribution to real Income Province. It pass through Increasing income from hotel management, restaurant business, consolation, transportation commerce, and also another business in that city. In this time, we must expand the Restriction ( control ) is very needed in expanding. And because of that we can try to strart expanding the riverbank area to be ane of potential nature tourism business in Samarinda City. This examine trying to research how to optimize Mahakam riverbank scope in Samarinda City, adapted with the potential and the problem inside. So we make on analysis scenery area, existence area analysist, preference area analyst, how to exploit the scope area analyst. This analyst process bring with deskriptif kualitatif based on existence area, growth and expand area.Based on the analysis we found something and strategy to expand the scope of scenery zone as follws : ( this zone include in all Slamet Riyadi street Karang Asam ) The view just for attracted but not so interested. The activity is ordinary from the cityzen, event activity, and visitors. Facilities not optimize, but it can expand with more high standard of facilities. The problem in scape exploit is a dirty area, parked problem, and trader side the river. The rule still by the grap, not in restriction even directive programe. The exploite strategy can be real by the planning strategy, exploite strategy and also control in scope area all of each grouping by exploite group zone.